Odpowiedzi

2010-02-06T22:56:23+01:00
A]
3x-4x+2x-5x+7=-4x+7

x=-1
-4×-1+7=11
x=0
-4×0+7=7
x=2,5
-4×2,5+7=-10+7=-3
b]
-3m-4n+3n+5m=2m-n
m=1
n=-2
2×1+2=0
m=-0,5
n=0,1

2×-0,5-0,1=-1-0,1=-1,1

c]
-13x-y-23x=6
-33x-y-6
x=0,02
y=³/₁₉
-33×0,02-³/₁₉-6=-0,66-6³/₁₉=-³³/₅₀-¹¹⁷/₁₉=-6⁷⁷⁷/₉₅₀

coś mi sie to nie podoba, ale też twój przykład nie był zbyt czytelnie napisany

x=0
y=1
-33×0-1-6=-7
Najlepsza Odpowiedź!
2010-02-06T22:56:49+01:00
A)
dla x = -1
3x-4x +2x-5x +7=-4x+7=-4(-1)+7=4+7=11
dla x + 0
3x-4x +2x-5x +7=-4x+7=-4(0)+7=0+7=7
dla x= 2,5
3x-4x +2x-5x +7=-4x+7=-4(2,5)+7=-10+7=-3
b)
dla m = 1 i n = -2
-3m-4n+3n+5m=2m-n=2(1)+2=4
dla m = - o,5 i n = o,1
-3m-4n+3n+5m=2m-n=2(-0,5)-0,1=-1-0,1=-1,1
C)
dla x = 0,02 i y + - trzy dziewiętnaste
-13x + y +23x - 20y + 6=-0,26 - 0,16 + 0,46 + 3,16 + 6
= 9,2
dlax = 0 i y = 1
-13x + y +23x - 20y + 6=0+1+0-20+6=-13
2010-02-06T23:09:25+01:00
A)
3x-4x +2x-5x +7
dla x = -1
3*(-1) - 4*(-1) + 2*(-1) - 5*(-1) + 7
-3 + 4 - 2 + 5 + 7
= 11

3x-4x +2x-5x +7
dla x = 0
3*0 - 4*0 + 2*0 - 5*0 + 7
= 7

3x-4x +2x-5x +7
dla x= 2,5
3*2,5 - 4*2,5 + 2*2,5 - 5*2,5 + 7
7,5 - 10 + 5 - 12,5 + 7
= -3

b)
-3m-4n+3n+5m
dla m = 1 i n = -2
-3*1 - 4*(-2) + 3*(-2) + 5*1
-3 + 8 - 6 + 5
= 4

-3m-4n+3n+5m
dla m = - 0,5 i n = 0,1
-3*(-0,5) - 4*0,1 + 3*0,1 + 5*(-0,5)
1,5 - 0,4 + 0,3 - 2,5
= -1,1

c)
-13x + y + 23x - 20y + 6
dla x = 0,02 i y = - trzy dziewiętnaste
-13*0,02 +(-3/19) + 23*0,02 - 20*(-3/19) + 6
-0,26 - 0,16 + 0,46 + 3,16 + 6
= 9,2

-13x + y + 23x - 20y + 6
dla x = 0 i y = 1
-13*0 + 1 + 23*0 - 20*1 + 6
1 + 6
= 7